A method for rapid preparation of lithium-philic three-dimensional carbon conductive framework

By using graphene skeletons in lithium metal batteries and forming nano-gold particles through microwave reaction, the problems of uneven deposition of lithium and lithium dendrites are solved, and the high energy density and excellent electrochemical properties of lithium metal batteries are achieved.

CN115249815BActive Publication Date: 2025-02-18HUANENG CLEAN ENERGY RES INST
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211014762.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-23
Publication Date
2025-02-18
Estimated Expiration
2042-08-23

AI Technical Summary

Technical Problem

Lithium metal batteries face uneven lithium deposition, resulting in lithium dendrites growth, safety issues and SEI film breakage, affecting battery capacity and Coulomb efficiency.

Method used

Graphene is used as a flexible conductive three-dimensional carbon skeleton, and the gold source is introduced and reduced to nano-gold particles through microwave reactions, as a nucleation inducer for lithium, improving the lithium-philic characteristics of the carbon skeleton.

Benefits of technology

Through the uniform distribution of nano-gold particles inside the carbon skeleton, the uniform deposition of lithium is promoted, the growth of lithium dendrites is inhibited, the electrochemical performance of lithium metal negative electrodes is improved, and the lithium metal battery with ultra-high energy density is realized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115249815B_ABST
    Figure CN115249815B_ABST
Patent Text Reader

Abstract

The invention discloses a method for rapidly preparing a lithium-philic three-dimensional carbon conductive skeleton, comprising the following steps: stirring and mixing graphene and a gold source in a solvent, and obtaining a solid powder after drying; pressing the solid powder into an electrode piece; placing the electrode piece in an inert gas or nitrogen atmosphere, and performing a microwave reaction at a power of 100 to 1000 W, and obtaining the lithium-philic three-dimensional carbon conductive skeleton after reacting for 10 to 600 seconds; the gold source is any one of chloroauric acid and gold chloride or a mixture of the two. The method of the invention uses graphene as a flexible conductive three-dimensional carbon skeleton, and introduces a gold source at the same time, and reduces the gold source in situ into nano-gold through microwave reaction, so as to serve as a nucleation inducer of lithium, which is distributed inside the carbon skeleton, improves the lithium-philic property of the carbon skeleton, and promotes the uniform deposition of lithium, thereby effectively inhibiting the growth of lithium dendrites, and the microwave reduction reaction is short in time and low in energy consumption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of energy storage batteries, and in particular, relates to a method for rapidly preparing a lithium-philic three-dimensional carbon conductive skeleton. Background Art

[0002] Lithium metal has the lightest mass (0.537 g / cm 3 ), the lowest potential (-3.04V vs.H / H + ) and extremely high specific capacity (3860mAh / g, equivalent to 10 times that of commercial negative electrodes), it is a very promising negative electrode. Lithium metal batteries can achieve high energy density, effectively reduce the unit battery cost of fixed energy storage systems, reduce the space share of mobile energy storage, increase its unit energy density, and enhance its application potential.

[0003] Despite such attractive application prospects, lithium metal anodes still face serious challenges. First, uneven lithium deposition will cause uncontrollable lithium dendrite growth, eventually causing a short circuit and causing safety problems. Secondly, due to the ultra-high activity of lithium metal, an uneven solid electrolyte interface (SEI film) will be formed between lithium metal and the electrolyte surface. Compared with the graphite anode, which only changes in volume by 10%, the lithium metal anode has no main body, so huge volume changes will occur during the deposition and stripping process. Unlimited volume expansion will seriously aggravate the fracture of the brittle SEI film. The continuous rupture and regeneration of the SEI film leads to electrolyte consumption, accelerates the growth of lithium dendrites, and generates a large amount of "dead" lithium that is separated from the matrix, which damages the battery capacity and coulomb efficiency. Therefore, inhibiting the growth of lithium dendrites is an urgent problem to be solved for lithium metal batteries.

[0004] Constructing a three-dimensional conductive host skeleton (3D host) is an important solution strategy. The 3D conductive skeleton can provide abundant space to alleviate the volume change of the electrode during charging and discharging. Its large specific surface area can reduce the local current density and help the uniform deposition of lithium metal. However, the most widely studied 3D metal porous current collectors (Cu and Ni foams) will significantly reduce the energy density of the battery pack and cannot be applied to commercial batteries. Therefore, a flexible three-dimensional carbon skeleton with high specific surface area, light weight, and rich conductive network is a better choice. Unfortunately, carbon-based materials are generally not compatible with lithium. The deposition of lithium depends largely on the initial nucleation. The lithium-phobic characteristics of carbon-based materials will cause a large nucleation barrier, which will greatly hinder the subsequent uniform nucleation and growth of lithium. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, an embodiment of the present invention provides a method for rapidly preparing a lithium-philic three-dimensional carbon conductive framework, comprising the following steps:

[0006] (1) stirring and mixing graphene and a gold source in a solvent to obtain a solid powder after drying;

[0007] (2) pressing the solid powder obtained in step (1) into a pole piece;

[0008] (3) placing the electrode in an inert gas or nitrogen atmosphere and subjecting it to a microwave reaction at a power of 50 to 1000 W, and reacting for 10 to 600 seconds to obtain the lithium-philic three-dimensional carbon conductive framework;

[0009] The gold source is any one of chloroauric acid and gold chloride or a mixture of the two.

[0010] The method for rapidly preparing a lithium-philic three-dimensional carbon conductive skeleton in an embodiment of the present invention adopts a flexible and lightweight carbon material graphene as a flexible conductive three-dimensional carbon skeleton, introduces a gold source and uniformly mixes it with the gold source, and reduces the gold source in situ into nano-gold particles by microwave reaction and by means of the wave-absorbing property of graphene, so as to serve as a nucleation inducer of lithium and uniformly distribute the gold source inside the carbon skeleton, thereby improving the lithium-philic property of the carbon skeleton; and fully utilizes the huge specific surface area and three-dimensional space of the three-dimensional graphene, thereby adjusting the internal charge distribution, inhibiting the charge tip effect, and further promoting the uniform deposition of lithium metal and inhibiting the growth of lithium dendrites; in addition, compared with the traditional chemical reduction method, the embodiment of the present invention utilizes microwave reduction to obtain nano-gold, which is simpler, more efficient, and has lower energy consumption.

[0011] In some embodiments, in step (1), the gold source is preferably chloroauric acid; the solvent is one or a mixed solution of two or more of water, ethanol, acetonitrile, N,N-dimethylformamide, preferably a mixed solution of water and ethanol.

[0012] In some embodiments, in step (1), the mass ratio of the graphene to the gold source is 2:1 to 10:1, preferably 4:1.

[0013] In some embodiments, in step (3), the power of the microwave reaction is preferably 100 to 500 W, and the reaction time is preferably 30 to 100 s.

[0014] In some embodiments, in step (1), the stirring speed is 10 to 500 rpm, preferably 200 to 300 rpm; the time is 1 to 24 hours, preferably 2 to 5 hours.

[0015] In some embodiments, in step (2), the pressing pressure is 1-40 MPa, preferably 10 MPa.

[0016] In some embodiments, in step (2), the pole piece has a diameter of 8 to 20 mm, preferably 10 to 16 mm, and a thickness of 50 to 500 μm, preferably 150 μm.

[0017] Another aspect of the embodiments of the present invention further provides a lithiophilic three-dimensional carbon conductive framework, wherein the lithiophilic three-dimensional carbon conductive framework is prepared by the above method.

[0018] The lithium-philic three-dimensional carbon conductive skeleton of the embodiment of the present invention uses a flexible and lightweight carbon material as a conductive skeleton, introduces a lithium nucleation inducer to improve the lithium-philic properties of the carbon skeleton, and graphene has a high specific surface area, which can provide more adsorption sites for nano-gold particles, making them evenly distributed inside the skeleton. During the electrochemical process, the local current density can be significantly reduced, and the uniform deposition of lithium can be promoted, thereby effectively inhibiting the growth of lithium dendrites.

[0019] Another aspect of the embodiments of the present invention further provides a lithium metal negative electrode, which is prepared by pre-storing lithium in the above-mentioned lithium-philic three-dimensional carbon conductive skeleton.

[0020] In the lithium metal negative electrode of the embodiment of the present invention, lithium is uniformly deposited in the three-dimensional carbon skeleton, which inhibits the growth of lithium dendrites. At the same time, the flexible characteristics of three-dimensional graphene can effectively buffer the stress changes caused by volume changes during lithium deposition / stripping, thereby improving the electrochemical performance of the lithium metal negative electrode.

[0021] In some embodiments, the lithium pre-storage method is electrochemical lithium pre-storage or molten lithium infiltration.

[0022] An embodiment of the present invention also provides a lithium metal battery, wherein the negative electrode of the lithium metal battery is the above-mentioned lithium metal negative electrode, and the positive electrode is any one of a lithium iron phosphate positive electrode, a ternary positive electrode, a lithium iron manganese phosphate positive electrode or a sulfur positive electrode; the lithium metal battery can be used in an energy storage system.

[0023] The lithium metal battery of the embodiment of the present invention has excellent electrochemical performance and is expected to achieve ultra-high energy density (>300Wh / kg) lithium metal battery, improve the energy density per unit area of ​​fixed energy storage, and enhance the energy storage efficiency of mobile energy storage.

[0024] In some embodiments, the energy storage system is a fixed energy storage system and / or a mobile energy storage system.

[0025] The advantages and beneficial effects of the present invention are:

[0026] (1) The method for rapidly preparing a lithium-philic three-dimensional carbon conductive skeleton according to an embodiment of the present invention uses graphene as a flexible conductive three-dimensional carbon skeleton, and simultaneously introduces a gold source and reduces the gold source in situ into gold nanoparticles through microwave reaction by means of the wave-absorbing property of graphene. The gold source serves as a nucleation inducer for lithium and is evenly distributed inside the carbon skeleton, thereby improving the lithium-philic property of the carbon skeleton. Compared with the traditional chemical reduction method, the microwave reduction method according to the embodiment of the present invention takes a short time and only takes a few minutes to achieve gold reduction, which is more efficient, simple, low-energy-consuming, and suitable for large-scale production.

[0027] (2) The high specific surface area of ​​graphene materials provides a wide range of adsorption sites for gold nanoparticles, which can significantly reduce the local current density during the electrochemical process and promote the uniform deposition of lithium, thereby effectively inhibiting the growth of lithium dendrites. At the same time, the flexible characteristics of three-dimensional graphene can effectively buffer the stress changes caused by volume changes during lithium deposition / stripping, thereby improving the electrochemical performance of lithium metal negative electrodes.

[0028] (3) The lithium-philic three-dimensional carbon conductive skeleton of the embodiment of the present invention is used for lithium metal negative electrode, and has excellent electrochemical performance. It can be assembled with various positive electrodes such as lithium iron phosphate positive electrode, ternary positive electrode, lithium manganese iron phosphate positive electrode and sulfur positive electrode to form a lithium metal battery, which is expected to realize ultra-high energy density lithium metal battery, improve the energy density per unit area of ​​fixed energy storage, and enhance the energy storage efficiency of mobile energy storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a flow chart of preparing a lithium-philic three-dimensional carbon conductive framework by microwave reaction in Examples 1-3 of the present invention.

[0030] Figure 2 The lithium deposition behavior on the lithium-philic three-dimensional carbon conductive skeleton of Example 1 of the present invention and the graphene skeleton of Comparative Example 1 is shown; wherein, (a) is the lithium deposition behavior on the graphene skeleton of Comparative Example 1, and (b) is the lithium deposition behavior on the lithium-philic three-dimensional carbon conductive skeleton of Example 1.

[0031] Figure 3 This is the XRD spectrum of the lithium-philic three-dimensional carbon conductive skeleton prepared in Example 1 of the present invention.

[0032] Figure 4a This is a TEM image of the lithium-philic three-dimensional carbon conductive framework prepared in Example 1 of the present invention at low magnification.

[0033] Figure 4b The high-resolution image and selected area electron diffraction pattern image of the lithium-philic three-dimensional carbon conductive skeleton prepared in Example 1 of the present invention.

[0034] Figure 5a When the deposition is 3 mAh·cm -2 Lithium, deposition morphology of lithium in the graphene skeleton prepared in Comparative Example 1 at different magnifications.

[0035] Figure 5b When the deposition is 3 mAh·cm -2 Lithium, deposition morphology of lithium in the lithium-philic three-dimensional carbon conductive framework prepared in Example 1 of the present invention at different magnifications.

[0036] Figure 6 These are the cycle performance test diagrams of AGLi / Li symmetric batteries and CuLi / Li symmetric batteries.

[0037] Figure 7 The test graphs show the specific capacity and coulombic efficiency of AGLi / LFP full battery and CuLi / LFP full battery. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described below. Obviously, the described embodiment is a part of the embodiment of the present invention, not all the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention.

[0039] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by those having ordinary skills in the field to which the present invention belongs.

[0040] An embodiment of the present invention provides a method for rapidly preparing a lithium-philic three-dimensional carbon conductive framework, comprising the following steps:

[0041] (1) stirring and mixing graphene and a gold source in a solvent to obtain a solid powder after drying;

[0042] (2) pressing the solid powder obtained in step (1) into a pole piece;

[0043] (3) placing the electrode in an inert gas or nitrogen atmosphere and subjecting it to a microwave reaction at a power of 50 to 1000 W, and reacting for 10 to 600 seconds to obtain the lithium-philic three-dimensional carbon conductive framework;

[0044] The gold source is any one of chloroauric acid (HAuCl4·3H2O), gold chloride (AuCl3) or a mixture of the two.

[0045] Since carbon materials have the property of hating lithium, despite being highly conductive, lithium cannot be deposited inside the three-dimensional graphene skeleton. During the charge and discharge process, lithium tends to be deposited outside the three-dimensional carbon skeleton and cannot fully utilize its internal space. However, through microwave reaction, the gold source in the three-dimensional carbon skeleton can be reduced to nano-gold in situ. The binding energy of nano-gold with lithium affinity (3.06eV) is higher than that of graphene (1.91eV). Since lithium will preferentially deposit at high binding energy sites, when nano-gold is evenly dispersed inside graphene, lithium will be deposited at the nano-gold particle sites inside the three-dimensional carbon skeleton. The high specific surface area of ​​graphene materials provides a wide range of adsorption sites for nano-gold particles, which can significantly reduce the local current density during the electrochemical process, promote the uniform deposition of lithium, and thus effectively inhibit the growth of lithium dendrites.

[0046] The method for rapidly preparing a lithium-philic three-dimensional carbon conductive skeleton in an embodiment of the present invention utilizes microwave reaction to reduce a gold source into nano-gold to serve as a nucleation inducer for lithium, which is evenly distributed inside the carbon skeleton, thereby improving the lithium-philic properties of the carbon skeleton. Compared with traditional chemical reduction, microwave reaction reduction is faster, and nano-gold can be obtained in just a few minutes, which is highly efficient and has low energy consumption.

[0047] In some embodiments, in step (1), the gold source is preferably chloroauric acid (HAuCl4·3H2O); the solvent is one or a mixed solution of two or more of water (H2O), ethanol (C2H5OH), acetonitrile (CH3CN), N,N-dimethylformamide (C3H7NO), preferably a mixed solution of water (H2O) and ethanol (C2H5OH).

[0048] In some embodiments, in step (1), the mass ratio of graphene to gold source is 2:1 to 10:1, for example, 2:1, 3:1, 4:1, 5:1, 7:1, 9:1, 10:1, etc.; preferably, the mass ratio of graphene to gold source is 4:1.

[0049] In some embodiments, in step (3), the power of the microwave reaction is preferably 100-500 W, for example, 100 W, 200 W, 250 W, 300 W, 400 W, 450 W, 500 W, etc.; the reaction time is preferably 30-100 s, for example, 30 s, 40 s, 50 s, 65 s, 80 s, 100 s, etc.

[0050] In some embodiments, in step (1), the stirring speed is 10 to 500 rpm, for example, 10 rpm, 60 rpm, 100 rpm, 150 rpm, 200 rpm, 300 rpm, 320 rpm, 400 rpm, 500 rpm, etc.;

[0051] Preferably, the stirring rotation speed is 200-300 rpm, for example, 200 rpm, 220 rpm, 250 rpm, 280 rpm, 300 rpm, etc.

[0052] In some embodiments, in step (1), the stirring time is 1 to 24 hours, for example, 1 hour, 2 hours, 5 hours, 8 hours, 10 hours, 15 hours, 18 hours, 20 hours, 24 hours, etc.;

[0053] Preferably, the stirring time is 2 to 5 hours, for example, 2 hours, 2.5 hours, 3 hours, 4 hours, 5 hours, etc.

[0054] In some embodiments, in step (1), drying is performed under light-proof conditions; the drying method is freeze-drying or vacuum drying, preferably freeze-drying.

[0055] In some embodiments, in step (2), the pressing pressure is 1 to 40 MPa, for example, 1 MPa, 5 MPa, 10 MPa, 12 MPa, 20 MPa, 25 MPa, 40 MPa, etc., preferably 10 MPa.

[0056] In some embodiments, in step (2), the diameter of the pole piece is 8 to 20 mm, for example, 8 mm, 10 mm, 12 mm, 15 mm, 18 mm, 20 mm, etc.;

[0057] Preferably, the diameter of the pole piece is 10-16 mm, for example, 10 mm, 12 mm, 15 mm, 16 mm, etc.

[0058] In some embodiments, in step (2), the thickness of the pole piece is 50 to 500 μm, for example, 50 μm, 100 μm, 120 μm, 150 μm, 200 μm, 350 μm, 500 μm, etc., preferably 150 μm.

[0059] In some embodiments, in step (3), the inert gas is helium or argon, preferably argon.

[0060] like Figure 1 As shown in the flow chart of preparing a lithium-philic three-dimensional carbon conductive skeleton by microwave reaction, the method for rapidly preparing a lithium-philic three-dimensional carbon conductive skeleton in an embodiment of the present invention can realize the in-situ reduction of the gold source on the graphene three-dimensional skeleton with the help of the microwave energy field. Compared with traditional electrochemical reduction, microwave reduction is simpler and more efficient.

[0061] Another aspect of the embodiments of the present invention further provides a lithiophilic three-dimensional carbon conductive framework, which is prepared by the above method.

[0062] The lithium-philic three-dimensional carbon conductive skeleton of the embodiment of the present invention uses a flexible and lightweight carbon material as a conductive skeleton, introduces a lithium nucleation inducer to improve the lithium-philic properties of the carbon skeleton, and graphene has a high specific surface area, which can provide more adsorption sites for nano-gold particles, making them evenly distributed inside the skeleton. During the electrochemical process, the local current density can be significantly reduced, and the uniform deposition of lithium can be promoted, thereby effectively inhibiting the growth of lithium dendrites.

[0063] Another aspect of the embodiments of the present invention further provides a lithium metal negative electrode, which is prepared by pre-storing lithium in the above-mentioned lithium-philic three-dimensional carbon conductive skeleton.

[0064] In the lithium metal negative electrode of the embodiment of the present invention, lithium is uniformly deposited in the three-dimensional carbon skeleton, which inhibits the growth of lithium dendrites. At the same time, the flexible characteristics of three-dimensional graphene can effectively buffer the stress changes caused by volume changes during lithium deposition / stripping, thereby improving the electrochemical performance of the lithium metal negative electrode.

[0065] In some embodiments, the method of pre-storing lithium is electrochemical pre-storage of lithium or molten lithium infiltration; wherein, electrochemical pre-storage of lithium: lithium metal is used as a lithium source and a counter electrode, a lithium storage body is used as a working electrode, and lithium deposition is performed on the lithium storage body by constant current discharge; molten lithium infiltration: molten lithium is placed on the surface of the lithium storage body and the temperature is maintained until all the lithium is melted and infiltrated into the interior of the lithium storage body.

[0066] An embodiment of the present invention also provides a lithium metal battery, the negative electrode of which is the above-mentioned lithium metal negative electrode, and the positive electrode is any one of a lithium iron phosphate positive electrode, a ternary positive electrode, a lithium iron manganese phosphate positive electrode or a sulfur positive electrode; it can be used in an energy storage system.

[0067] In some embodiments, the energy storage system is a fixed energy storage system or a mobile energy storage system.

[0068] The lithium metal battery of the embodiment of the present invention has excellent electrochemical performance and is expected to achieve ultra-high energy density (>300Wh / kg) lithium metal battery, improve the energy density per unit area of ​​fixed energy storage, and enhance the energy storage efficiency of mobile energy storage.

[0069] The present invention is further described in detail below with reference to specific embodiments.

[0070] Example 1

[0071] A method for rapidly preparing a lithium-philic three-dimensional carbon conductive framework comprises the following steps:

[0072] (1) Add 160 mg of graphene and 40 mg of chloroauric acid to a mixture of 30 mL of water and ethanol, stir magnetically at 200 rpm for 3 h, and then freeze-dry for 10 h to obtain a solid powder;

[0073] (2) Under a pressure of 10 MPa, the solid powder obtained in step (1) is pressed into a pole piece with a diameter of 12 mm and a thickness of 150 μm;

[0074] (3) The electrode is placed in a sealed argon atmosphere, put into a microwave oven, and the power is set to 450 W for microwave reaction. The reaction time is 30 seconds, and a lithium-philic three-dimensional carbon conductive skeleton can be prepared.

[0075] Figure 2 (b) shows the deposition behavior of lithium on the lithium-philic three-dimensional carbon conductive skeleton of this embodiment. It can be seen that when the evenly distributed lithium-philic nanogold is introduced into the three-dimensional carbon conductive skeleton, the binding energy of the lithium-philic nanogold (3.06eV) is higher than that of graphene (1.91eV). Since lithium will preferentially deposit at high binding energy sites, when the nanogold is uniformly dispersed inside the graphene, lithium will preferentially deposit on the surface of the nanogold, that is, inside the three-dimensional carbon conductive skeleton, thereby making full use of the huge specific surface area of ​​the three-dimensional carbon conductive skeleton, thereby effectively reducing the critical current density, promoting the uniform deposition of lithium and inhibiting the formation of lithium dendrites, and obtaining a high-performance lithium metal negative electrode.

[0076] Figure 3 The XRD pattern of the lithium-philic three-dimensional carbon conductive skeleton prepared in this embodiment is as follows: Figure 3 It can be seen that after microwave reaction, the gold source in the three-dimensional carbon conductive skeleton is reduced to nano-gold.

[0077] Figure 4a This is a TEM image of the lithium-philic three-dimensional carbon conductive framework obtained in this example at low magnification. Figure 4b The high-resolution image and selected area electron diffraction pattern of the lithium-philic three-dimensional carbon conductive skeleton prepared in this embodiment (shown in the inset) are shown in FIG. Figure 4a and Figure 4b It can be seen that under the microscopic perspective, nanogold particles of uniform size are evenly distributed on graphene.

[0078] Figure 5b When the deposition is 3 mAh·cm -2 The lithium deposition morphology of the lithium-philic three-dimensional carbon conductive skeleton prepared in this embodiment at different magnifications shows that when gold nanoparticles are introduced into the three-dimensional carbon conductive skeleton, all the lithium is deposited inside the three-dimensional skeleton, thereby effectively inhibiting the growth of lithium dendrites.

[0079] Example 2

[0080] A method for rapidly preparing a lithium-philic three-dimensional carbon conductive framework comprises the following steps:

[0081] (1) Add 200 mg of graphene and 40 mg of chloroauric acid to a mixture of 30 mL of water and ethanol, stir magnetically at 200 rpm for 3 h, and then freeze-dry for 10 h to obtain a solid powder;

[0082] (2) Under a pressure of 12 MPa, the solid powder obtained in step (1) is pressed into a pole piece with a diameter of 12 mm and a thickness of 150 μm;

[0083] (3) The electrode is placed in a sealed argon atmosphere, put into a microwave oven, and the power is set to 450 W for microwave reaction. The reaction time is 30 seconds, and a lithium-philic three-dimensional carbon conductive skeleton can be prepared.

[0084] Example 3

[0085] A method for rapidly preparing a lithium-philic three-dimensional carbon conductive framework comprises the following steps:

[0086] (1) Add 160 mg of graphene and 40 mg of chloroauric acid to a mixture of 30 mL of water and ethanol, stir magnetically at 200 rpm for 3 h, and then freeze-dry for 10 h to obtain a solid powder;

[0087] (2) Under a pressure of 10 MPa, the solid powder obtained in step (1) is pressed into a pole piece with a diameter of 12 mm and a thickness of 150 μm;

[0088] (3) The electrode is placed in a sealed argon atmosphere, put into a microwave oven, and the power is set to 300 W for microwave reaction. The reaction time is 30 seconds, and a lithium-philic three-dimensional carbon conductive skeleton can be prepared.

[0089] Comparative Example 1

[0090] A method for preparing a graphene skeleton comprises the following steps: pressing 160 mg of graphene into a pole piece with a diameter of 12 mm and a thickness of about 150 μm to obtain a graphene skeleton.

[0091] Figure 2 (a) shows the deposition behavior of lithium on the graphene skeleton of this comparative example. As can be seen from the figure, due to the lithium-phobic property of graphene, lithium cannot be fully deposited inside the three-dimensional skeleton, but is preferentially deposited on the outer surface in a limited space. Therefore, it still faces a series of challenges such as lithium dendrite growth and "dead lithium" generation.

[0092] Figure 5a When the deposition is 3 mAh·cm -2 The lithium deposition morphology of the graphene skeleton prepared in Comparative Example 1 at different magnifications shows that in the lithium-phobic three-dimensional graphene skeleton, lithium is only partially deposited inside the three-dimensional structure of the graphene skeleton, and a large amount of lithium is preferentially deposited on the surface of the graphene three-dimensional skeleton.

[0093] Experimental Example 1: Symmetrical Battery Performance Test

[0094] The lithiophilic three-dimensional carbon conductive framework (AG) prepared in Example 1 of the present invention was heated at 1 mA·cm -2 The current density was 5 mAh·cm -2 of lithium metal to form a lithium metal anode (AGLi).

[0095] Preparation of AGLi / Li symmetrical battery: The lithium metal negative electrode and lithium metal electrode prepared above are used as the working electrode and the counter electrode respectively to assemble into a symmetrical battery (AGLi / Li).

[0096] Preparation of CuLi / Li symmetric battery: -2 The current density was 5 mAh·cm -2 The lithium metal is used as the working electrode (CuLi), and the lithium metal electrode is used as the counter electrode to assemble a symmetrical battery (CuLi / Li).

[0097] The electrolyte used in the above two symmetrical batteries is 1M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) in 1,3-dioxolane (DOL) / ethylene glycol dimethyl ether (DME) (volume ratio 1:1) solution.

[0098] Symmetrical battery test: at 3mA·cm -2 The current density of 1 mAh cm -2 The charge and discharge cycle performance of AGLi / Li symmetrical battery and CuLi / Li symmetrical battery was tested at a cycle capacity of Figure 6 As shown, the results show that the polarization voltage of the AGLi / Li symmetric battery remains basically stable, showing good cycle characteristics.

[0099] Experimental Example 2: Full Battery Performance Test

[0100] Preparation of AGLi / LFP full battery: The lithiophilic three-dimensional carbon conductive framework (AG) prepared in Example 1 of the present invention was charged at 1 mA·cm -2 The current density of pre-deposition was 3 mAh cm -2 The lithium is used as the battery negative electrode AGLi, and is assembled with the lithium iron phosphate positive electrode into a full battery.

[0101] Preparation of CuLi / LFP full battery without 3D conductive skeleton: -2 The current density of the deposited sample was 3 mAh cm -2 The lithium CuLi is used as the battery negative electrode, and is assembled into a full battery with the lithium iron phosphate positive electrode.

[0102] The electrolyte used in the above two full batteries is 1M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) in 1,3-dioxolane (DOL) / ethylene glycol dimethyl ether (DME) (volume ratio 1:1) solution.

[0103] The above-mentioned AGLi / LFP full battery and CuLi / LFP full battery were tested for specific capacity and coulombic efficiency. The test voltage range was 2.5-4.0V and the current density was 0.5C. The full battery discharge specific capacity and coulombic efficiency were as follows: Figure 7 As shown. Figure 7 It can be seen that after 300 cycles at a current density of 0.5C, the coulombic efficiency of the two full batteries is comparable, basically reaching more than 99.9%; but the discharge specific capacity of the two full batteries is different. Under the same conditions, after 300 cycles, the specific capacity of the CuLi / LFP full battery decays to a certain extent, while the specific capacity of the AGLi / LFP full battery is relatively stable and exhibits a higher specific capacity.

[0104] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0105] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for rapidly preparing a lithium-philic three-dimensional carbon conductive framework, characterized in that: The following steps are involved: (1) stirring and mixing graphene and a gold source in a solvent to obtain a solid powder after drying; (2) pressing the solid powder obtained in step (1) into a pole piece; (3) placing the electrode in an inert gas or nitrogen atmosphere and subjecting it to a microwave reaction at a power of 50 to 1000 W, and reacting for 10 to 600 seconds to obtain the lithium-philic three-dimensional carbon conductive framework; The gold source is any one of chloroauric acid and gold chloride or a mixture of the two.

2. The method for rapidly preparing a lithium-philic three-dimensional carbon conductive framework according to claim 1, characterized in that: In step (1), when the gold source is chloroauric acid, the mass ratio of the gold source to the graphene is 1:2 to 1:10; and the solvent is one or a mixed solution of two or more of water, ethanol, acetonitrile, and N,N-dimethylformamide.

3. The method for rapidly preparing a lithium-philic three-dimensional carbon conductive framework according to claim 1, characterized in that: In step (3), the power of the microwave reaction is 100 to 500 W, and the reaction time is 30 to 100 s.

4. The method for rapidly preparing a lithium-philic three-dimensional carbon conductive framework according to claim 1, characterized in that: In step (1), the stirring speed is 10 to 500 rpm and the time is 1 to 24 hours.

5. The method for rapidly preparing a lithium-philic three-dimensional carbon conductive framework according to claim 1, characterized in that: In step (2), the pressing pressure is 1 to 40 MPa.

6. The method for rapidly preparing a lithium-philic three-dimensional carbon conductive framework according to claim 1, characterized in that: In step (2), the pole piece has a diameter of 8 to 20 mm and a thickness of 50 to 500 μm.

7. A lithium-philic three-dimensional carbon conductive framework, characterized in that The lithium-philic three-dimensional carbon conductive framework is prepared by the method according to any one of claims 1 to 6.

8. A lithium metal negative electrode, characterized in that The lithium-philic three-dimensional carbon conductive skeleton described in claim 7 is pre-stored with lithium to form the lithium metal negative electrode.

9. The lithium metal negative electrode according to claim 8, characterized in that The method of pre-storing lithium is electrochemical pre-storing lithium or molten lithium infiltration.

10. A lithium metal battery, characterized in that: The negative electrode of the lithium metal battery is the lithium metal negative electrode as claimed in claim 8, and the positive electrode is any one of a lithium iron phosphate positive electrode, a ternary positive electrode, a lithium iron manganese phosphate positive electrode or a sulfur positive electrode.

Citation Information

Patent Citations

  • Three-dimensional high-density metal nanoparticle / graphene porous composite as well as preparation method and application thereof

    CN108711611A